Heat and mass exchange analysis indoors - Єрохін, А. Л.; Зацеркляний, Г. А. (National Academy of Sciences of Ukraine, 2016)
We examine a non-stationary three-dimensional turbulent motion of the solid medium of two-component steam-air mixture in the presence of internal sources and drains of energy that allows to determine integral characteristics of thermal conditions in the lodging more exactly.
Keywords: non-stationary three-dimensional turbulent motion; steam-air mixture